Macular changes following cataract surgery in eyes with early diabetic retinopathy: an OCT and OCT angiography study - Yao, Huiping; Yang, Zijian; Cheng, Yu; Shen, Xi (Frontiers in Medicine, 2023)
Background: To evaluate changes in macular status and choroidal thickness (CT) following phacoemulsification in patients with mild to moderate nonproliferative diabetic retinopathy (NPDR) using optical coherence tomography. Methods: In this prospective study, all of the patients underwent uncomplicated phacoemulsification. Retinal superficial capillary plexus vascular density (SCP-VD), macular thickness (MT), and CT were measured pre- and postoperatively. Results: Twenty-two eyes of 22 cataract patients with mild to moderate NPDR without diabetic macular edema (DME) and 22 controls were enrolled. BCVA increased in two groups at 3 months postoperatively. At 1 and 3 months postoperatively, SCP-VD in the diabetic retinopathy (DR) group significantly increased; changes in SCP-VD in parafovea were significantly greater in the DR group than in the control group. MT and CT in the DR group significantly increased at all visits postoperatively in the fovea and perifovea. Changes in parafoveal MT were significantly greater in the DR group than in the control group at all visits postoperatively. Changes in CT and MT in the fovea were significantly greater in patients with DR than in the controls 1 and 3 months postoperatively. Conclusions: Uncomplicated phacoemulsification resulted in greater increases in SCP-VD, MT and CT in patients with early DR without preoperative DME than in controls.